2022
DOI: 10.1007/s10029-022-02599-6
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in abdominal wall hernia: let’s ask patients what matters to them?

Abstract: Introduction Quality of Life (QoL) is an important consideration in patients with abdominal wall hernia (AWH). What matters to patients and their everyday experience living with AWH may depend on a variety of personal, psychological, social and environmental factors. At present, no study has addressed what is important to this particular group of patients by asking the patients themselves. This study aims to determine QoL from the patient’s perspective by examining the lived experience in this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The results presented here are only the mental health aspects of QoL deemed important by AWH patients, with other themes reported elsewhere [ 13 ]. Three key themes pertaining to how AWH affected patients’ mental health were identified: “psychological and emotional distress”, “identity disruption” and “coping mechanisms and support systems”.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The results presented here are only the mental health aspects of QoL deemed important by AWH patients, with other themes reported elsewhere [ 13 ]. Three key themes pertaining to how AWH affected patients’ mental health were identified: “psychological and emotional distress”, “identity disruption” and “coping mechanisms and support systems”.…”
Section: Resultsmentioning
confidence: 89%
“…A letter of invitation along with an information sheet pertaining to the study and interviews was arranged. A more detailed overview of the research process is provided in the in-depth report of various key indicators concerning AWH patients’ quality of life [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Incisional hernias may occur after open abdominal surgery and can impact on patient's body image, symptom burden and mental health. 12 Furthermore, the cost of repairing an abdominal wall hernia can range from $7500 to $18 000 United States Dollars. 13 A robotic approach does not entirely mitigate the risk of hernia but can reduce the risk due to the smaller incisions made.…”
Section: Discussionmentioning
confidence: 99%
“…Open abdominal surgery is associated with abdominal wall morbidity, which can lead to significant costs for patients. Incisional hernias may occur after open abdominal surgery and can impact on patient's body image, symptom burden and mental health 12 . Furthermore, the cost of repairing an abdominal wall hernia can range from $7500 to $18 000 United States Dollars 13 .…”
Section: Discussionmentioning
confidence: 99%
“…They also experienced overwhelming frustration due to the symptoms of their condition like low mood, depression, anxiety. Thus, hernias can affect the quality of lives in many aspects (Ahmed Alenazi et al, 2017; Smith et al, 2022). Mosco study revealed that 20.9% of the population had abdominal wall hernias.…”
Section: Introductionmentioning
confidence: 99%